2015
DOI: 10.1590/s0080-623420150000700017
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of Nursing Activities Score among Intensive Care Unit health professionals

Abstract: Objective: To analyze the interrater reliability of NAS among critical care nurses and managers in an ICU. Method: This was a methodological study performed in an adult, general ICU in Norway. In a random selection of patients, the NAS was scored on 101 patients by three raters: a critical care nurse, an ICU physician and a nurse manager. Interrater reliability was analyzed by agreement between groups and kappa statistics. Results: The mean NAS were 88.4 (SD=16.2) and 88.7 (SD=24.5) respectively for the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
5
1
2
Order By: Relevance
“…This length of stay was higher than that observed in other studies, 6,20 and can be explained by the clinical complexity of the trauma patient, although the majority of the patients are young, which would mean a faster recovery. Regarding their discharge from the ICU, 81.00% of the patients survived and 19.00% did not survive; a result that shows that the mortality was low in comparison to another investigation.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…This length of stay was higher than that observed in other studies, 6,20 and can be explained by the clinical complexity of the trauma patient, although the majority of the patients are young, which would mean a faster recovery. Regarding their discharge from the ICU, 81.00% of the patients survived and 19.00% did not survive; a result that shows that the mortality was low in comparison to another investigation.…”
contrasting
confidence: 65%
“…The mean of the nursing workload was 73.40%, which was similar or higher than other Brazilian studies 1,6,17 and lower than what was found in a study in Norway. 20 This result is important, although it does show that trauma ICU patients require intensive nursing care. In this way, knowing the NAS measure can contribute to developing strategies that aim at improving nursing care and adequate nursing design.…”
mentioning
confidence: 99%
“…The results are low for the items with categories of an estimated time by nurses (e.g. present at bedsite and observation for two hours or more) ( Stuedahl et al, 2015 ). This subjective estimation can lead to differences in Nursing Activities Score -scores and subsequently to differences in the calculated need for nursing staff ( Ducci and Padilha, 2008 , Carmona-Monge et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Presenting scores from several raters might have strengthened the results. One reliable method, in which a health professional scored the same patient as the other raters, was used in a study of inter-rater reliability (Stuedahl et al, 2015). One earlier study conducted a pre-test (reliability) of understanding of each item in the NAS (Ducci & Padilha, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study revealed that the inter-rater concordance and intra-class correlation were high between nurse-raters (Valls-Matarin et al, 2015). Findings from Norway (Stuedahl et al, 2015) on the inter-rater reliability between health professionals (i.e., critical care nurses) reported a mean NAS of 88.4%, whereas physicians had a significantly lower mean of 83.7%. This result can be converted to time and is equivalent to a difference of 1 hr per 24 hr for each patient.…”
Section: Revised Manuscriptmentioning
confidence: 95%